Conceito de área: uma proposta de ensino-aprendizagem - Facco, Sonia Regina (2003)
The objective of the research is to study phenomena that influence the teaching and learning of the concept of area in Ensino Fundamental (students aged 7-15). It presents a teaching proposal for the concept of area and a reflection about the learning of this concept through a teaching sequence involving the decomposition and composition of plane figures. The following hypothesis guided the development of the different activities proposed: problem situations involving determining the areas of geometrical figures, in particular areas of polygons, permits comparisons of these figures using area as magnitude. to study area as magnitude and the comparison of surfaces by cutting and pasting or tiling enables the understanding of this concept. a proposal for teaching and learning the concept of area, involving the decomposition and composition of figures, provides favourable conditions for the learning of the concept of area. The theoretical basis for the research is proved principally by the tool-object dialectic and the change of frameworks of Régine Douady (1986) and the theory of semiotic representation registers of Raymond Duval (1993,1994,1995). The methodology used follows the principles of didactic engineering. The research involved teachers of the fifth to eighth grade and students of the eighth grade